ANALISIS KONTRASTIF AFIKSASI (PREFIKS) VERBA BAHASA JAWA SERANG DENGAN BAHASA INDONESIA - Safitri, Restu; Rosidin, Odien (Universitas Batanghari, 2023)
This study is to examine the contrastive form of verb affixation, describe verb affixation, and find the differences and similarities between Serang Javanese and Indonesian. The purpose of this research is to easing language learning so that it can optimally avoid interference. This research uses qualitative approach with qualitative descriptive method. The data collection in this research is made by listening, reading and comprehending then doing note-taking technique which is recording the findings of verb affixation in dictionary or daily conversation. The theory used is the theory of contrastive analysis by comparing B-1 and B-2 to find similarities and differences. The result shows that there are similarities and differences between verb affixation in Serang Javanese and Indonesian. One of the similarities occurs in the prefix di-, and the differences are found in the prefixes tak- and ke-. The prefixes nge-, ng-, ny, and N- in Serang Javanese can be matched in form and meaning with the prefix me- in Indonesian which means active verb or expresses an action.